Denmark : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that the Danish economy is recovering slowly and unevenly. The economy contracted slightly in 2013, but it looks likely to accelerate modestly in 2014. Growth is held down by a trend decline in North Sea oil and gas production as well as exports to euro-area partners. At the same time, private domestic demand and non-oil exports are supporting growth. The recovery is likely to continue but remain fragile. Annual growth is estimated at 0.7 percent in 2014, projected to increase to 1.4 percent in 2015, and trend to slightly above 2 percent thereafter.